Design and Fabrication of Shoe/Slippers Sanitizing Ramp (American Journal of Innovation in Science and Engineering, 2023)
This paper describes the design and development of a low-cost shoe and slippers sanitizing ramp and proposes an innovative design using a conventional switching unit to operate the device. User acceptance, technical performance, and cost analysis are presented through surveys and testing. The project development study was realized as a disinfecting device by modification of a manually-operated sanitizing ramp. It uses a 12volt converter-charger and or storage battery as a pump power source, 20-70 kg/m working pressure pump unit, 0.10mm diameter with one-hole brass misting nozzles and conventional switches mounted in the 12kg wheeled main frame. The technical evaluation result shows that misting nozzle sprays are limited to 10-20cc/min. Regarding cost, it is just a portion of the cost compared to the commercially available and electronically-operated model. The developed sanitizing ramp offers an option for users who cannot pay for or buy the commercially available one.